One-Year Outcome of Combination Therapy with Full or Reduced Photodynamic Therapy and One Anti-Vascular Endothelial Growth Factor in Pachychoroid Neovasculopathy - Miki Sato-Akushichi; Shinji Ono; Tatsuro Taneda; Gerd Klose; Asuka Sasamori; Youngseok Song (MDPI AG, 2022)
This paper evaluates a one-year treatment outcome after full or reduced photodynamic therapy (PDT) and anti-vascular endothelial growth factor (VEGF) combination therapy for pachychoroid neovasculopathy (PNV). After the initial combination therapy, a total of 29 eyes from 29 patients (16 for full treatment and 13 for reduced treatment), exhibited reduced, central retinal thickness and central choroidal thickness, and the improvements were maintained for 1 year after the initial combination therapy. Twenty-two eyes (75.9%) required no additional treatments for 1 year. The recurrence rate was 31.3% in the full treatment and 15.4% in the reduced treatment, with no significant differences between them. One shot of anti-VEGF and full or reduced PDT combination therapy had similar efficacy in treating PNV. Further prospective, large-scale, and long-term studies are required to determine a better treatment for PNV.